Iron-based alloys and alloy powders
The iron-based alloy with a specific composition addresses the challenge of maintaining amorphous phases in manufacturing, achieving enhanced mechanical and chemical properties, particularly in high-temperature oxidation resistance and wear resistance.
Patent Information
- Application Number
- JP2023507410
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-03
- Filing Date
- 2021-08-04
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-08-04
AI Technical Summary
Existing amorphous alloys face challenges in maintaining a high proportion of amorphous phases during manufacturing, leading to reduced mechanical and chemical properties, such as corrosion resistance and abrasion resistance.
An iron-based alloy composition containing specific weight ratios of iron, chromium, molybdenum, and niobium, which enhances amorphous formation ability and improves mechanical and chemical properties like oxidation resistance and wear resistance.
The iron-based alloy powder exhibits excellent amorphous formation ability, resulting in improved mechanical and chemical properties, including high-temperature oxidation resistance and wear resistance, making it suitable for various applications.
Smart Images

Figure 0007656025000005 
Figure 0007656025000006 
Figure 0007656025000007
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an iron-based alloy and alloy powder, and more particularly to an alloy that has excellent amorphous-forming ability, excellent wear resistance and corrosion resistance, and can be used for various purposes, and an alloy powder produced therefrom. [Background technology]
[0002] An amorphous alloy is an alloy in which the metal atoms contained in the alloy are not in a crystalline structure but in a disordered and chaotic structure. Amorphous alloys have excellent chemical, electrical and mechanical properties and are being researched for various applications, but they have limitations such as difficulty in forming and difficulty and cost in manufacturing, and there have been few cases of commercialization to date.
[0003] In order to produce an amorphous alloy, two conditions must be met: an alloy composition with high amorphous-forming ability is required, and a rapid cooling rate of the molten alloy is required. In other words, rapid cooling of the molten alloy material is required, and if the amorphous-forming ability of the alloy material composition is low even after rapid cooling, it is possible that the amorphous phase will not be formed.
[0004] In particular, when alloy powder made of an amorphous alloy is used to manufacture products such as coatings or compacts, the alloy powder is often cooled at a sufficient rate after melting, which means that crystallization rather than amorphization occurs, resulting in a problem that the ratio of the amorphous phase in the product decreases rapidly, making it difficult to manufacture applied products that utilize the properties of the amorphous alloy material.
[0005] Due to these problems, when an amorphous alloy is used to manufacture a molded body or form a coating layer, the ratio of the amorphous phase is low, and the desired physical properties of the product cannot be obtained, or the density is poor, corrosion resistance is reduced, and foreign matter is easily penetrated.
[0006] Therefore, there is a need to study alloys that maintain a high ratio of amorphous phase and can improve the microstructure and mechanical properties, as well as application methods of such alloys. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent No. 10-0723167 Summary of the Invention [Problem to be solved by the invention]
[0008] The object of the present invention is to develop an alloy that has excellent amorphous-forming ability and can produce a high amorphous ratio when used for a variety of applications and purposes, and to provide an alloy powder that can be produced from the alloy and has improved mechanical and chemical properties, particularly oxidation resistance, wear resistance, and corrosion resistance at high temperatures.
[0009] Another object of the present invention is to provide an alloy powder which has excellent oxidation stability, is less susceptible to oxidation during use, and has a low ratio of oxides contained in an alloy coating layer. [Means for solving the problem]
[0010] The iron-based alloy according to one embodiment of the present invention is For 100 parts by weight of iron (Fe), Chromium (Cr) 17.22 to 58.23 parts by weight, 1.20 to 26.10 parts by weight of molybdenum (Mo), and It may contain 0.12 to 6.22 parts by weight of niobium (Nb).
[0011] The iron-based alloy powder according to another aspect of the present invention is For 100 parts by weight of iron (Fe), Chromium (Cr) 17.22 to 58.23 parts by weight, 1.20 to 26.10 parts by weight of molybdenum (Mo), and Niobium (Nb) 0.12 to 6.22 parts by weight, It may contain an amorphous phase. Effect of the Invention
[0012] An iron-based alloy according to one embodiment of the present invention comprises iron, chromium, molybdenum, and niobium, wherein each of the constituent elements is contained in a predetermined weight ratio, and has excellent amorphous-forming ability during product formation, and excellent chemical properties such as oxidation resistance and corrosion resistance, and mechanical properties such as hardness and wear resistance.
[0013] The iron-based alloy powder according to another aspect of the present invention has a composition including iron, chromium, molybdenum, and niobium, and can be used in various methods such as additive manufacturing, powder metallurgy, powder injection, or thermal spray coating. Since a product manufactured using the iron-based alloy powder has a composite structure including both an amorphous phase and ceramic crystals, the product has the advantages of excellent oxidation resistance, wear resistance, and high temperature properties.
[0014] In particular, the iron-based alloy powder according to one embodiment of the present invention has a very low mass increase rate due to oxidation at high temperatures, so there are almost no problems caused by oxide formation during use of the alloy powder, and the oxidation resistance and wear resistance at high temperatures are improved. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a diagram showing the results of observing the cross sections of the powders of Example 3 and Comparative Example 1. [Diagram 2] 1 is a graph showing the results of particle size analysis of the powders of Example 3 and Comparative Example 1. [Diagram 3] FIG. 2 is a diagram showing the results of observing the alloy powders of Example 3 and Comparative Example 1 by XRD analysis. [Figure 4] FIG. 2 is a diagram showing the results of observing the alloy powders of Example 3 and Comparative Example 1 with an electron probe microanalyzer (EPMA) analyzer. BEST MODE FOR CARRYING OUT THEINVENTION
[0016] Before describing the present invention in detail, it should be noted that the terminology used in this specification is for the purpose of describing specific implementations, and is not intended to limit the scope of the present invention, which is limited only by the scope of the appended claims. All technical and scientific terms used in this specification may be interpreted as having the same meaning as commonly understood by those of ordinary skill in the art, unless otherwise specified.
[0017] Hereinafter, examples of the implementation of the present invention and technical effects thereof will be described with reference to the accompanying drawings.
[0018] The iron-based alloy according to one embodiment of the present invention can contain iron (Fe), chromium (Cr), molybdenum (Mo), and niobium (Nb). The iron-based alloy according to one embodiment of the present invention has the advantage of being excellent in terms of rigidity and economy of the alloy, since it contains iron as a metal constituting the alloy.
[0019] Chromium may be included in iron-based alloys to improve their physical or chemical properties, such as wear resistance and corrosion resistance.
[0020] In order to ensure amorphous forming ability and wear resistance, chromium may be contained in a range of 17.22 parts by weight or more per 100 parts by weight of iron. It may be contained in a range of 18.32 parts by weight or more, and more preferably in a range of 21.96 parts by weight or more. On the other hand, if chromium is contained excessively, there is a concern that the formation of intermetallic compounds will lead to an increase in brittleness and a decrease in corrosion resistance, so chromium may be contained in a range of 58.23 parts by weight or less per 100 parts by weight of iron. It may be contained in a range of 44.25 parts by weight or less, and more preferably in a range of 34.11 parts by weight or less.
[0021] Chromium may be present in the iron-based alloy at a level of 14.5 wt% or more, preferably at a level of 15 wt% or more, and more preferably at a level of 17 wt% or more, while chromium may be present in the iron-based alloy at a level of 29 wt% or less, preferably at a level of 25 wt% or less, and more preferably at a level of 22 wt% or less.
[0022] Molybdenum may be added to improve the wear, corrosion and friction resistance of iron-based alloys.
[0023] To achieve such an effect, molybdenum may be contained in an amount of 1.2 parts by weight or more relative to 100 parts by weight of iron, preferably 2.44 parts by weight or more, and more preferably 4.52 parts by weight or more.
[0024] On the other hand, if molybdenum is contained in an excessive amount, it may not dissolve in the base material but may diffuse and precipitate, which may deteriorate the thermal properties of the material, so molybdenum may be contained in the range of 26.10 parts by weight or less, preferably 19.47 parts by weight or less, and more preferably 12.40 parts by weight or less, relative to 100 parts by weight of iron.
[0025] Molybdenum may be present in the iron-based alloy at a level of 1 wt% or less, preferably 2 wt% or more, and more preferably 3.5 wt% or more, while molybdenum may be present in the iron-based alloy at a level of 13 wt% or less, preferably 11 wt% or less, and more preferably 8 wt% or less.
[0026] Niobium is an element that dissolves in the substrate structure and greatly improves the high-temperature stability of the substrate. It has the properties of not reacting with oxygen in the air at high temperatures, not reacting with most chemicals, and not corroding.
[0027] To achieve such an effect, niobium may be contained in the range of 0.12 parts by weight or more relative to 100 parts by weight of iron, preferably 0.61 parts by weight or more, and more preferably 1.29 parts by weight or more.
[0028] On the other hand, if niobium is contained in an excessive amount, the niobium that is not dissolved in the substrate may segregate at the substrate interface or form additional phases, which may reduce high-temperature safety and high-temperature oxidation resistance, so niobium may be contained in a range of 6.22 parts by weight or less relative to 100 parts by weight of iron, preferably 5.31 parts by weight or less, and more preferably 3.10 parts by weight or less.
[0029] Niobium may be included in the iron-based alloy at a level of 0.1 wt% or more, preferably 0.5 wt% or more, and more preferably 1 wt% or more. Meanwhile, niobium may be included in the iron-based alloy at a level of 3.1 wt% or less, preferably 3 wt% or less, and more preferably 2 wt% or less. In addition, the iron-based alloy according to one aspect of the present invention may further include any one or more selected from boron (B), carbon (C), and silicon (Si).
[0030] Boron can improve the amorphous forming ability of the alloy by making the grain size difference between metal atoms and the alloy mismatch and efficient packing, and also form borides to improve the mechanical properties and wear resistance of the material.
[0031] To achieve such an effect, boron may be contained in the range of 0.12 parts by weight or more relative to 100 parts by weight of iron, preferably 0.61 parts by weight or more, and more preferably 1.29 parts by weight or more.
[0032] On the other hand, if boron is included in an excessive amount, the amount of solid-solubilized elements in the metal substrate may decrease due to the excessive formation of borides, which may decrease the chemical stability and excessively increase the brittleness of the material, so boron may be included in a range of 6.63 parts by weight or less relative to 100 parts by weight of iron, preferably 5.31 parts by weight or less, and more preferably 3.88 parts by weight or less.
[0033] Boron may be present in the iron-based alloy at a level of 0.1 wt% or more, preferably 0.5 wt% or more, and more preferably 1 wt% or more, while boron may be present in the iron-based alloy at a level of 3.3 wt% or less, preferably 3 wt% or less, and more preferably 2.5 wt% or less.
[0034] Like boron, carbon can improve the amorphous forming ability of the alloy by allowing mismatching and efficient packing due to the difference in particle size with metal atoms in the alloy. In addition, if the amount of carbon added is below a certain level, carbon is not uniformly distributed in the base material, which may cause local variations in mechanical properties of the material. Therefore, carbon may be included in a range of 0.12 parts by weight or more, preferably 0.13 parts by weight or more, per 100 parts by weight of iron.
[0035] On the other hand, if carbon is contained in an excessive amount, carbides are formed in an excessive amount, and the effect of solid solution strengthening of the base material cannot be fully exerted, which may result in a deterioration of the mechanical properties of the material, so carbon may be contained in a range of 3.61 parts by weight or less relative to 100 parts by weight of iron, preferably 2.65 parts by weight or less, and more preferably 1.55 parts by weight or less.
[0036] Carbon may be present in the iron-based alloy at a level of 0.1 wt% or more, while carbon may be present in the iron-based alloy at a level of 1.8 wt% or less, preferably 1.5 wt% or less, and more preferably 1.0 wt% or less.
[0037] The iron-based alloy according to one embodiment of the present invention may contain, relative to 100 parts by weight of iron, 17.22 to 58.23 parts by weight of chromium, 1.2 to 26.1 parts by weight of molybdenum, and 0.12 to 6.22 parts by weight of niobium, and may further contain one or more selected from 0.12 to 6.63 parts by weight of boron and 0.12 to 3.61 parts by weight of carbon.
[0038] Preferably, the iron-based alloy may contain, relative to 100 parts by weight of iron, 18.32 to 44.25 parts by weight of chromium, 2.44 to 19.47 parts by weight of molybdenum, 0.61 to 5.31 parts by weight of niobium, 0.61 to 5.31 parts by weight of boron, and 0.12 to 2.65 parts by weight of carbon.
[0039] More preferably, the iron-based alloy may contain, relative to 100 parts by weight of iron, 21.96 to 34.11 parts by weight of chromium, 4.52 to 12.40 parts by weight of molybdenum, 1.29 to 3.10 parts by weight of niobium, 1.29 to 3.88 parts by weight of boron, and 0.13 to 1.55 parts by weight of carbon.
[0040] The iron-based alloy according to an embodiment of the present invention may further include at least one selected from tungsten (W), cobalt (Co), yttrium (Y), manganese (Mn), aluminum (Al), zirconium (Zr), phosphorus (P), nickel (Ni), and scandium (Sc) in addition to the above-mentioned alloy components, and these additional components may be included in a lower content than the above-mentioned iron, chromium, molybdenum, boron, and carbon. The iron-based alloy according to an embodiment of the present invention may include some impurities that are inevitably introduced during the manufacturing process.
[0041] In addition, since silicon (Si) is an element that is disadvantageous to the expression of amorphous forming ability and high-temperature oxidation resistance, the iron-based alloy according to one embodiment of the present invention does not artificially add silicon, and even if it is inevitably introduced, the content is suppressed as much as possible. Silicon may be contained in an amount of 0.2 parts by weight or less per 100 parts by weight of iron. It may be contained in an amount of 0.1 parts by weight or less, and more preferably 0.05 parts by weight or less. It may be contained in an amount of 0 parts by weight or less. Meanwhile, silicon may be contained in an amount of 0.5 times or less, preferably 0.3 times or less, and more preferably 0.1 times or less, the weight of carbon contained in the iron-based alloy.
[0042] The iron-based alloy according to one embodiment of the present invention may have a ratio of the weight of chromium to the weight of molybdenum (Cr / Mo) in the range of 3 to 5. When the content ratio of chromium to molybdenum satisfies the range, a better amorphous forming ability can be ensured, and advantageous effects such as improved chemical and mechanical properties such as oxidation resistance, wear resistance, and hardness can be obtained. A preferable ratio of the weight of chromium to the weight of molybdenum may be 3.5 to 4.75, and a more preferable ratio may be 3.75 to 4.25. The iron-based alloy according to one embodiment of the present invention has an advantage of excellent amorphous forming ability to form an amorphous phase, since it contains elements according to the above-mentioned composition.
[0043] The iron-based alloy powder according to an embodiment of the present invention may be manufactured from the iron-based alloy described above. The iron-based alloy powder according to an embodiment of the present invention may have the same composition as the iron-based alloy described above, but may further include some other components that are introduced by cooling or oxidation during the manufacture of the alloy powder. The iron-based alloy powder according to an embodiment of the present invention may include an amorphous phase due to the excellent amorphous forming ability of the raw material.
[0044] The iron-based alloy powder according to one embodiment of the present invention can be manufactured with various particle sizes and shapes depending on the application and application method such as 3D printing, powder metallurgy, injection, mold, thermal spray coating, etc., and the particle size and shape are not particularly limited. For example, it can have a particle size distribution of 1 to 150 μm, preferably 10 to 100 μm. The alloy powder used for thermal spray coating can have an average particle size of 10 to 54 μm, preferably 16 to 43 μm, and the alloy powder used for metal injection (MIM) can have an average particle size of 20 μm or less, preferably 5 to 16 μm.
[0045] For alloy powders used in 3D printing, fine powders with an average particle size of 20μm or less are preferred for powder bed fusion 3D printing, and coarse powders with an average particle size of 150-430μm, preferably 50-100μm, are preferred for direct energy deposition (DED) 3D printing, etc. For alloy powders used in laser cladding, alloy powders of similar size to those used in the DED method can be used.
[0046] If the particle size distribution and average size of the alloy powder are outside the above ranges, it may be difficult to obtain uniform quality when manufacturing products using the alloy powder, and the efficiency of the work may decrease.
[0047] The method for producing the iron-based alloy powder according to an embodiment of the present invention is not particularly limited, and may be, for example, a water atomizing method or a gas atomizing method.
[0048] The atomizing method may refer to a method in which, when a molten alloy is dropped, gas or water is sprayed to break it into small particles, and the broken droplets of alloy powder are rapidly cooled to produce alloy powder. Those skilled in the art can easily understand and repeatedly implement the atomizing method without the addition of special technical means.
[0049] The iron-based alloy powder according to one embodiment of the present invention may include alpha-iron (α-Fe) having an amorphous phase and a body-centered cubic (BCC) crystal structure.
[0050] The iron-based alloy powder according to one embodiment of the present invention may include one or more of an iron-based boride or a chromium-based boride.
[0051] The iron-based borides and chromium-based borides can be interpreted as including any of iron borides, chromium borides, and borides of iron and chromium.
[0052] The chromium contained in the alloy powder can be present in the form of boride without being dissolved in the iron base material or iron matrix. The iron-based alloy powder can contain 30 to 90 area % of iron borides and chromium-based borides. The area % may be preferably 35 to 85 area %, and more preferably 40 to 80 area %.
[0053] Molybdenum or niobium borides may not be present in the alloy powder, or may be present at undetectable levels.Molybdenum or niobium contained in the iron-based alloy powder may exist as a solid solution in the iron-based matrix.
[0054] Since the iron-based alloy powder according to one embodiment of the present invention is manufactured from an iron-based alloy having excellent amorphous forming ability, an amorphous phase or a metallic glass phase may be observed at least in a part of the cross section of the alloy powder. The presence or absence of the amorphous phase or the metallic glass phase can be confirmed by EBSD or TEM.
[0055] The iron-based alloy powder according to one embodiment of the present invention has the above-mentioned composition and contains an amorphous phase in at least a part of its region, and therefore has excellent oxidation resistance. That is, the iron-based alloy powder according to one embodiment of the present invention can be formed to have a low oxidation rate at high temperatures, a small total oxidation amount, and a high critical temperature at which rapid oxidation occurs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0056] The present invention will be described in more detail below with reference to examples. However, it should be noted that the following examples are for the purpose of illustrating the present invention and the scope of the present invention is not limited to the following examples.
[0057] <Example> Examples 1 to 7: Production of alloy powder Materials were weighed to have a predetermined composition and then melted to obtain an iron-based alloy. The obtained molten alloy was supplied to an atomizer in a gas atmosphere and atomized, and the split molten metal droplets were cooled to produce alloy powders of Examples 1 to 7. The alloy components and average diameters of the powders of Examples 1 to 7 are as shown in Table 1 below.
[0058] Examples 8 to 12: Formation of alloy coating layer using HVOF method Using the alloy powders of Examples 1, 2, 5, 6 and 7, an alloy coating layer having a thickness shown in Table 2 was formed by an ultra-high velocity flame spraying (HVOF, High velocity oxygen fuel spray) method using oxygen and propane gas as fuels at a spray distance of 30 cm using an ultra-high velocity flame spraying device (Oerlikon Metco Diamond Jet series HVOF gas fuel spray system). The device and conditions used in this case are specifically described below.
[0059] -DJ Gun HVOF- [Conditions] Gun type: Hybrid, Air cap: 2701, LPG Flow: 160SCFH, LPG Pressure: 90PSI, Oxygen flow: 550SCFH, Oxygen Pressure: 150PSI, Air flow: 900SCFH, Air Pressure: 100PSI, Nitrogen flow: 28SCFH, Nitrogen Pressure: 150PSI, Gun speed: 100m / min, Gun pitch: 3.0mm, Feeder rate: 45g / min, Stand-off distance: 250mm
[0060] <Comparative Example> Comparative Examples 1 to 5: Production of alloy powder The iron-based alloys were weighed according to a predetermined composition, melted, and then fed to an atomizer in a nitrogen gas atmosphere to produce alloy powders of Comparative Examples 1 to 5. The alloy components and average powder diameters of Comparative Examples 1 to 5 are as shown in Table 1 below.
[0061] Comparative Examples 6 to 10: Formation of alloy coating layer The alloy powders of Comparative Examples 1 to 5 were coated in the same manner as in Examples 8 to 12 to obtain the alloy coating layers of Comparative Examples 6 to 10 shown in Table 2.
[0062] [Table 1]
[0063] [Table 2]
[0064] <Experimental Example> Experimental example 1: Particle size analysis of alloy powder The grain sizes of the alloy powders of Example 3 and Comparative Example 1 were analyzed, and the cross sections of the powders were observed with an electron microscope (SEM). Figure 1 shows the results of observing the cross sections of the powders of Example 3(a) and Comparative Example 1(b), and Figure 2 is a graph showing the grain size analysis results of these powders.
[0065] As shown in Figures 1(a) and 2(a), the alloy powder of Example 3 is a spherical powder having a particle size distribution of 11.2 to 81.1 μm, and as shown in Figures 1(b) and 2(b), the alloy powder of Comparative Example 1 is a spherical powder having a particle size distribution of 11.2 to 81.2 μm.
[0066] Experimental Example 2: XRD crystal analysis of alloy powder The alloy powders of Example 3 and Comparative Example 1 were observed by XRD (X-ray diffraction) analysis, and the results are shown in FIG.
[0067] In both Example 3 and Comparative Example 1, Fe and Cr having a body-centered cubic (bcc) structure, and Fe-based borides were detected.
[0068] Experimental Example 3: Observation of the microstructure of alloy powder The alloy powders of Example 3 and Comparative Example 1 were observed with an electron probe microanalyzer (EPMA) analyzer, and the results shown in FIG. 4 were obtained.
[0069] In both Example 3 and Comparative Example 1, it can be confirmed that alpha-iron (α-Fe(BCC)), a Cr base material, and a Cr-based boride phase are present inside the spherical powder.
[0070] Experimental Example 4: Evaluation of the oxidation characteristics of alloy powders 50g of the alloy powders of Examples 1 to 7 and Comparative Examples 1 to 5 were placed in an Al2O3 pot, and the weight change during heating was observed using a TG-DTA 8122 device manufactured by Rigaku. The heating rate was set to 10°C / min, and the stop temperature was set to 1200°C. The powder was heated from room temperature to 1200°C, and the change in mass was observed. The weight of each powder was measured at room temperature and at 1200°C, and the weight was calculated based on the weight at room temperature and the weight at 1200°C. The weight increase at 1200°C relative to the weight at room temperature was converted to a weight increase ratio (%) and is also shown in Table 3. In addition, the temperature at the point where oxidation increased rapidly and the weight of the powder increased rapidly (weight increase conversion temperature, °C) was measured, and the temperature was also shown in Table 3 below.
[0071] [Table 3]
[0072] Experimental Example 5: Evaluation of wear resistance of alloy coating layer The wear resistance of the alloy coating layers of Examples 8 to 12 and Comparative Examples 6 to 10 was evaluated. Using a wear tester (Pin on disc wear test machine, RB-102PD), the layers were rubbed against Si3N4 at room temperature with a load of 5 kgf and a speed of 0.05 m / s to measure the degree of wear, and the results are shown in Table 4 below.
[0073] [Table 4]
[0074] Experimental Example 6: Measurement of amorphous ratio of alloy coating layer The alloy coating layers of Examples 8 to 12 and Comparative Examples 6 to 10 were analyzed for crystallinity by electron backscatter diffraction (EBSD) using a nordlys CMOS detector (step size: 0.05 μm).
[0075] EBSD analysis revealed that the (Cr,Fe)2B and Fe(BCC) phases were commonly observed. The specific amorphous phase ratios for each specimen are also listed in Table 4 above.
[0076] As shown in Tables 3 and 4, the examples satisfying the alloy composition of the present invention have a weight gain of 1.5% or less at 1200°C and a conversion temperature of weight gain of 1000°C or more, whereas the comparative examples not satisfying the alloy composition of the present invention have a weight gain of more than 1.5% at 1200°C and a conversion temperature of weight gain of less than 1000°C. In addition, the examples satisfying the alloy composition of the present invention have an amorphous phase ratio of more than 7 area% in the coating layer and a wear amount of the coating layer of 1.0 mm. 3 In contrast, in the comparative example not satisfying the alloy composition of the present invention, the ratio of the amorphous phase in the coating layer was less than 7% by area, and the wear amount of the coating layer was 1.0 mm 3 That is, the examples satisfying the alloy composition of the present invention are excellent not only in high-temperature oxidation resistance but also in amorphous-phase forming ability, whereas the comparative examples not satisfying the alloy composition of the present invention are relatively inferior in high-temperature oxidation resistance or amorphous-phase forming ability.
[0077] The features, structures, effects, etc. exemplified in each of the above-described embodiments can be combined or modified in other embodiments by a person having ordinary skill in the art to which the embodiments belong. Therefore, the contents related to such combinations and modifications should be interpreted as being included in the scope of the present invention.
Claims
1. A material consisting of iron (Fe), chromium (Cr), molybdenum (Mo), niobium (Nb), boron (B), carbon (C) and unavoidable impurities; For 100 parts by weight of iron (Fe), Chromium (Cr) 17.22 to 58.23 parts by weight, Molybdenum (Mo) 1.20 to 26.10 parts by weight, Niobium (Nb) 0.12 to 6.22 parts by weight, Boron (B) 0.12 to 6.63 parts by weight, and An iron-based alloy containing 0.12 to 3.61 parts by weight of carbon (C), An iron-based alloy, comprising an alloy powder having an average particle size of 31.9 to 35.0 μm, and the alloy powder is heated at a temperature increase rate of 10° C. / min from room temperature to 1200° C., and the weight increase rate of the alloy powder is measured to be 1.5% or less.
2. An iron-based alloy as described in claim 1, wherein the silicon content of the impurities is limited to 0.2 parts by weight or less (including 0) per 100 parts by weight of the iron.
3. A material comprising iron (Fe), chromium (Cr), molybdenum (Mo), niobium (Nb), boron (B), carbon (C) and unavoidable impurities; For 100 parts by weight of iron (Fe), Chromium (Cr) 17.22 to 58.23 parts by weight, Molybdenum (Mo) 1.20 to 26.10 parts by weight, Niobium (Nb) 0.12 to 6.22 parts by weight, Boron (B) 0.12 to 6.63 parts by weight, and Contains 0.12 to 3.61 parts by weight of carbon (C); An iron-based alloy powder comprising an amorphous phase, An iron-based alloy powder, wherein after obtaining an alloy powder portion having an average particle size of 31.9 to 35.0 μm, the alloy powder is heated at a temperature increase rate of 10° C. / min from room temperature to a temperature range of 1200° C., and the weight increase rate of the alloy powder is measured to be 1.5% or less.
4. 4. The iron-based alloy powder of claim 3, wherein the iron-based alloy powder comprises an iron-based boride or a chromium-based boride.
5. The iron-based alloy powder according to claim 3 , wherein the iron-based alloy powder includes a solid solution formed by the molybdenum or the niobium being dissolved in the iron.
6. The iron-based alloy powder according to claim 3, wherein the average particle size of the iron-based alloy powder is 10 to 54 μm.
7. 4. The iron-based alloy powder of claim 3, wherein the iron-based alloy powder is used in HVOF spray or plasma spray coatings.
8. The iron-based alloy powder of claim 3, wherein the silicon content of the impurities is limited to 0.2 parts by weight or less (including 0) per 100 parts by weight of the iron.
Citation Information
Patent Citations
Ferrum-base block non-crystalline alloy material
CN101033530A
Cored wire for nanostructure-containing high-temperature oxidation corrosion resistant coating
CN103060737A
Alloy having extremely fine uniform dispersed crystal phase
JP1980145150A
Thermal spray material
JP1995316771A
Improvement of glass stability, glass formation ability, and microstructural refinement.
JP2008539327A